Analysis of Container Problems in Exception Area at PT. Terminal Petikemas Surabaya uses the Lean Six Sigma Method - Vivi Mentari Dewi; Iis Dewi Ratih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
PT Terminal Petikemas Surabaya is a company engaged in logistics, container services. Since the end of December 2019, PT Terminal Petikemas Surabaya began implementing a gate automation system at gate in exports. One thing that is done to support the gate automation is the Exception Area which is used as a data repair place for trucks that experience problems during the gate-in export process before heading to the stacking field. Containers that are constrained during the gate-in process indicate that there are procedural errors carried out by internal companies and external parties, such as drivers, forwarders, and importers related to administrative and technical problems. This research focuses on controlling the quality of container problems that enter the exception area by using a statistical method in the form of lean six sigma. The purpose of this study is to determine the average length of time to resolve containers for each problem, to know the quality of and the sigma level of the average length of time to resolve containers that enter the Exception Area based on the average number of container problems entering the Exception Area according to five problem criteria, knowing the problems that cause themost of the containers that enter the Exception Area. The results of the analysis in this study are the average length of time for containers that enter the Exception Area for each problem as a whole, the highest is caused by the system and the lowest is due to the closing time. The average number of container problems that enter the Exception Area in accordance with the five criteria, the problem has been controlled statistically with the most problem causes caused by the system, and the sigma level value is obtained from the average number of container problems that enter the Exception Area according to the five problem criteria which is 3,395, which means the variation or diversity of container problems that enter the exception area based on the problems of the containers that enter the Exception Area according to the five criteria, the problem is quite large.